2012
DOI: 10.2134/jeq2011.0317
|View full text |Cite
|
Sign up to set email alerts
|

The Availability of Copper in Soils Historically Amended with Sewage Sludge, Manure, and Compost

Abstract: Metals in soils amended with sewage sludge are typically less available compared with those in soils spiked with soluble metal salts. However, it is unclear if this difference remains in the long term. A survey of copper (Cu) availability was made in soils amended with sewage sludge, manure, and compost, collectively named organic amendments. Paired sets of amended and control soils were collected from 22 field trials where the organic amendments had aged up to 112 yr. Amended soils had higher total Cu concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Gemmatimonadetes copies g À1 soil Control 4.8 Â 10 8 AE 6 Â 10 7 5.1 Â10 8 AE 7 Â 10 7 5.6 Â 10 8 AE 6 Â 10 7 4.5 Â 10 8 AE 3 Â 10 7 Biochar 3.6 Â 10 8 AE 4 Â 10 7 5.0 Â 10 8 AE 6 Â 10 7 4.9 Â 10 8 AE 7 Â 10 7 4.9 Â 10 8 AE 6 Â 10 7 Compost 5.5 Â 10 8 AE 5 Â 10 7 4.6 Â 10 8 AE 3 Â 10 7 6.6 Â 10 8 AE 9 Â 10 7 6.8 Â 10 8 AE 8 Â 10 7 Biochar-compost 4.7 Â 10 8 AE 5 Â 10 7 6.4 Â 10 8 AE 9 Â 10 7 5.9 Â 10 8 AE 5 Â 10 7 5.9 Â 10 8 AE 7 Â 10 7 seen in the lab and in this study a neutral soil pH in addition to organic matter, either as biochar, compost or plant biomass, may have led to similar levels of immobilization across all plots (Smolders et al, 2012;Ruyters et al, 2013). That ability of organic matter to bind with Cu is discussed in Section 4.2.…”
Section: Copper Bioavailabilitysupporting
confidence: 55%
See 1 more Smart Citation
“…Gemmatimonadetes copies g À1 soil Control 4.8 Â 10 8 AE 6 Â 10 7 5.1 Â10 8 AE 7 Â 10 7 5.6 Â 10 8 AE 6 Â 10 7 4.5 Â 10 8 AE 3 Â 10 7 Biochar 3.6 Â 10 8 AE 4 Â 10 7 5.0 Â 10 8 AE 6 Â 10 7 4.9 Â 10 8 AE 7 Â 10 7 4.9 Â 10 8 AE 6 Â 10 7 Compost 5.5 Â 10 8 AE 5 Â 10 7 4.6 Â 10 8 AE 3 Â 10 7 6.6 Â 10 8 AE 9 Â 10 7 6.8 Â 10 8 AE 8 Â 10 7 Biochar-compost 4.7 Â 10 8 AE 5 Â 10 7 6.4 Â 10 8 AE 9 Â 10 7 5.9 Â 10 8 AE 5 Â 10 7 5.9 Â 10 8 AE 7 Â 10 7 seen in the lab and in this study a neutral soil pH in addition to organic matter, either as biochar, compost or plant biomass, may have led to similar levels of immobilization across all plots (Smolders et al, 2012;Ruyters et al, 2013). That ability of organic matter to bind with Cu is discussed in Section 4.2.…”
Section: Copper Bioavailabilitysupporting
confidence: 55%
“…Moreover, it is possible that compost simply provided necessary substrates for bacteria to tolerate Cu, as their main Cu strategy is efflux pumps, which require large amounts of energy (Klein and Lewinson, 2011). However, Kostov and Van Cleemput (2001) and Smolders et al (2012) agree that the addition of organic matter has the potential to reduce the impact of Cu, but does not guarantee it even in soil with a neutral pH. This study found that microbial and chemical benefits from compost did not remain stable over time.…”
Section: Microbial Abundance and Activitymentioning
confidence: 82%
“…In Paraná, most of the sewage sludge is subjected to sanitization by a prolonged alkaline stabilization process (addition of lime aimed at raising the pH of the mixture to 12 and a curing period of 30 days) (Paraná, 2009). Thus, when applied to agricultural land, the alkaline sewage sludge has double action, it increases the soil pH (Berton;Poggere et al, 2012) and can be a micronutrients source (Smolders et al, 2012;Bittencourt et al, 2014). However, unlike mineral fertilizer, the chemical composition of sewage sludge is quite variable, which results in a high degree of uncertainty regarding the micronutrient supply.…”
Section: Dalpisol M Et Almentioning
confidence: 99%
“…The specific adsorption is one of the most important mechanisms for controlling Zn and Cu availability in soil. The Zn and Cu adsorption capacity varies depending on the texture, mineralogy, organic matter and pH (Arias et al, 2006;Casagrande;Soares;Mouta, 2008;Smolders et al, 2012), thus, the availability of these nutrients may vary from soil to soil. On the other hand, under natural acid soil condition the Mn usually has high availability, which may promote plants toxicity (Millaleo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…depend on the degree of availability of the copper. Fresh copper that is added to old organically amended soil is less available in the next few days than fresh copper added to unamended soils (Smolders et al, 2012). The relative availability (amended/spiked) increases with the age of the amendment.…”
Section: ) Ageingmentioning
confidence: 99%